1991
DOI: 10.1001/archsurg.1991.01410300094014
|View full text |Cite
|
Sign up to set email alerts
|

Primary Resection and Anastomosis in Obstructed Descending Colon due to Cancer

Abstract: Intraoperative colonic irrigation followed by one-stage resection is gaining popularity as the optimal surgical treatment for left-sided colonic obstruction. However, its efficacy and potential hazards have not been adequately tested in obstruction due to colonic cancer. We analyzed the early results of 23 consecutive patients with obstructive left-sided colonic carcinoma treated by primary resection and anastomosis following intraoperative antegrade colonic lavage. Two patients (8.6%) died, one from complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 19 publications
(5 reference statements)
0
16
0
1
Order By: Relevance
“…Moreover, many patients are unable to undergo planned rever- sal of the colostomy because of age, comorbidities and other reasons, and thus remain with permanent stoma [8] . Some surgeons perform a one-stage resection with primary anastomosis, but this approach is associated with a high risk for complications [26] . An Italian study has shown that SEMS placement does not exclude laparoscopic resection as a second step and this approach offers a faster recovery [10] .…”
Section: Controversiesmentioning
confidence: 99%
“…Moreover, many patients are unable to undergo planned rever- sal of the colostomy because of age, comorbidities and other reasons, and thus remain with permanent stoma [8] . Some surgeons perform a one-stage resection with primary anastomosis, but this approach is associated with a high risk for complications [26] . An Italian study has shown that SEMS placement does not exclude laparoscopic resection as a second step and this approach offers a faster recovery [10] .…”
Section: Controversiesmentioning
confidence: 99%
“…There is a 4% risk of developing an anastomotic leak, which requires another operation to take down the anastomosis and create a temporary colostomy (19,20). After emergency resection, the patient remains in the intensive care unit (ICU) for two days and then another 12 days in the surgical ward (3,21,22).…”
Section: Competing Strategies Rsmentioning
confidence: 99%
“…There are two options for one-stage operation: standard colectomy with on-table colonic lavage or subtotal colectomy. The safety of the colonic lavage technique has been well documented, with a mortality rate of less than 10% and an anastomotic leakage rate of 5% (79)(80)(81)(82). A prospective, randomized trial comparing subtotal colectomy with standard colectomy with colonic lavage showed that the two techniques have similar rates of complication and mortality (83).…”
Section: Obstructing Colon Carcinomasmentioning
confidence: 99%